Analisis Efektivitas Penerapan Hukum Pidana Dalam Pengawasan Tindak Pidana di Indonesia - Khairani, Khairani; Suhendar, Suhendar; Mohamad Ali Syaifudin; Ali Imron; Rahmida Erliyani (UNES Law Review, 2024)
Human trafficking is a serious crime that involves the exploitation of individuals The threat of imprisonment is a dominant feature of the Indonesian Criminal Code. Although imprisonment is a common punishment in most countries, its effectiveness has been a topic of debate for centuries. Therefore, it is imperative to identify alternative forms of custodial punishment to mitigate the negative consequences of imprisonment. This research utilizes a descriptive qualitative approach to provide a comprehensive overview of the current issues based on existing evidence. The results of this research revealed several key insights. The fundamental purpose of criminal supervision in the Indonesian criminal justice system is to protect the public from criminal acts in accordance with the principles of criminal law. The Draft National Criminal Code explains that supervision punishment is an alternative to imprisonment. Supervision punishment is an alternative form of punishment with the provision that the punishment imposed will not be implemented if the conditions are met, with a maximum probation period of three years. It is evident that conditional punishment as an alternative to deprivation of liberty punishment in the existing Criminal Code is inadequate in protecting individuals and criminal offenders. Therefore, the National Criminal Code must evolve to include alternative formulations, such as supervision punishment (probation), which has been successfully developed and implemented in various countries around the world. The fundamental purpose of supervision punishment is to replace deprivation of liberty/imprisonment, an approach that has resulted in poor outcomes for both the convicted person and society at large. Therefore, supervision punishment should be included as the main type of punishment in the upcoming National Criminal Code, serving as an effective and humane alternative to deprivation of liberty.